Affinity-binding immobilization of d-amino acid oxidase on mesoporous silica by a silica-specific peptide. (1st November 2019) - Wang, Miaomiao; Qi, Wenjing; Xu, Hongping; Yu, Huimin; Zhang, Shuliang; Shen, Zhongyao
Abstract: Enzyme immobilization is widely used for large-scale industrial applications. However, the weak absorption through physical methods limits the recovery ability. Here, affinity-binding immobilization of enzymes was explored using a silica-specific affinity peptide (SAP) as a fusion tag to intensify the binding force between the enzyme and mesoporous silica (MPS) carrier. d- amino acid oxidase (DAAO) of Rhodosporidium toruloides was used as a model enzyme. The optimal screened SAP (LPHWHPHSHLQP) was selected from a M13 phage display peptide library and fused to the C-terminal of DAAO to obtain fused DAAOs with one, two and three SAP tags, respectively. The activity of DAAO–SAP–MPS was superior comparing with DAAO–2SAP–MPS and DAAO–3SAP–MPS; meanwhile DAAO–SAP–MPS shows 36% higher activity than that of DAAO–MPS. Fusion with one SAP improved the thermal stability with a 10% activity increase for immobilized DAAO–SAP–MPS compared to that of DAAO–MPS at 50 °C for 3 h. Moreover, the activity recovery of immobilized DAAO–SAP–MPS was 25% higher in operation stability assessment after six-batch conversions of cephalosporin to glutaryl-7-amino cephalosporanic acid than that of DAAO–MPS.